Labor and Tax Implications in the Recruitment of Foreign Workers and the Peculiarities of the Member Countries of the Andean Community - Ramirez Punchin, Eddy Hills (2014)
This article pretends to explain a problematic that must be analyzed from two perspectives, Labor and Tax law; thereby it will provide adequate solutions. Therefore, the authors will board the problematic of labor migration specifically geared to the hiring of foreign workers and its taxations methods. Furthermore, the authors will explain that the determination of the condition of domiciled or not of the foreigner, is not sufficient with the analysis of the internal tax laws; in some cases it is also necessary to analyze international standards that favor the taxpayer.